A study of commodity debt: The case of Punjab province-Pakistan - Rana, Abdul Wajid (International Food Policy Research Institute, 2021)
The state intervention in the agriculture market and trade policies, including ad-ministered prices or protective trade policies, with the objective of supporting food secu-rity, income generation for growers, and affordability for consumers has a long history. Most of these have been phased out through the late 1980s and 1990s though, wheat (through domestic procurement, temporary import/export control imposing regulatory duties, and sub-sidized sales to select flour mills) and sugarcane (through import tariffs, as well as indicative prices and export subsidies) still are the two major crops with public intervention. In addition, import tariffs and other restrictions protecting dairy products and vegetable oils remains. Be-sides, there are input subsidies on fertilizers, electricity for water pumping1 or implicitly, on canal irrigation water.